Palladium cobalt oxide thin film, delafossite-type oxide thin film, schottky electrode having delafossite-type oxide thin film, method for producing palladium cobalt oxide thin film, and method for producing delafossite-type oxide thin film
By using the palladium-cobalt oxide film formed by the sputtering method in the Schottky electrode and subjecting heat treatment, the problem of insufficient heat resistance and reliability under high temperature and high output conditions is solved, and the effects of high conductivity and high thermal stability are achieved.
Patent Information
- Application Number
- CN202380052951.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-11
- Filing Date
- 2023-03-27
- Publication Date
- 2025-03-04
AI Technical Summary
The existing Schottky electrodes have problems with insufficient heat resistance and reliability under high temperature and high output conditions, especially when using semiconductors such as gallium oxide for excellent power devices, the performance of the electrode cannot be fully exerted.
A copper iron ore oxide film such as palladium-cobalt oxide (PdCoO2) is used as a Schottky electrode, and the film is formed by sputtering method, and heat treatment is performed to improve its conductivity and stability.
It realizes high conductivity and high thermal stability of palladium-cobalt oxide films, and is suitable for high temperature and high output power device applications, improving the heat resistance and reliability of Schottky electrodes.
Smart Images

Figure HDA0005235588820000011 
Figure HDA0005235588820000012 
Figure HDA0005235588820000021
Abstract
Description
Technical Field
[0001] The present invention relates to a palladium-cobalt oxide film, a delafossite-type oxide film, a Schottky electrode having the delafossite-type oxide film, a method for preparing the palladium-cobalt oxide film, and a method for preparing the delafossite-type oxide film. Background Art
[0002] For example, as disclosed in International Publication No. 2020 / 090491 (Patent Document 1), the demand for power devices (also referred to as power semiconductors, power devices, or power semiconductor devices) used in power converters such as inverters and converters is increasing due to the popularity of electric vehicles (EVs), etc. As oxides for power devices, gallium oxide is well known.
[0003] Non-patent document 1 discloses a highly conductive PdCoO2 ultra-thin film with a delafossite crystal structure as a transparent electrode. In non-patent document 1, a PdCoO2 thin film is manufactured by a pulsed laser deposition method (PLD method: pulsed-laser deposition). As a specific example, the following example is disclosed: under the conditions of a substrate temperature of 700°C and an oxygen partial pressure of 100mTorr, a PdCoO2 thin film is manufactured on an Al2O3 substrate by alternately irradiating a PdCoO2 polycrystalline target and a Pd-PdO mixed phase target with a KrF excimer laser. In addition, non-patent document 1 shows an AFM morphology image of a PdCoO2 thin film prepared by a pulsed laser deposition method. From the AFM morphology image, it can be seen that the width of the PdCoO2 crystal in the film is very small, about 100nm, the crystal height is about 3nm, and the unevenness (peak difference) of the thickness direction (height direction) of the film surface is about 4nm. Here, the crystal width refers to, for example, the length drawn vertically from the vertex to the opposite side thereof when the crystal cross section is a triangle. In addition, the PdCoO2 crystals in this film have a triangular shape.
[0004] Non-patent document 2 also discloses a PdCoO2 film prepared by a pulsed laser deposition method. Non-patent document 2 points out the following problem: the resistivity of the PdCoO2 film is higher than the resistivity of a single crystal of PdCoO2, which is based on grain boundary scattering and is a factor different from temperature dependence. It is difficult to avoid the formation of grain boundaries in the preparation of PdCoO2 heteroepitaxial films, so exploring the high conductivity of PdCoO2 in large-area test works will be limited by the capabilities of thin film technology.
[0005] Non-patent document 3 discloses an example of achieving a large Schottky barrier of 1.8 eV in a PdCoO2 film. In addition, the PdCoO2 film was prepared by a pulsed laser deposition method. Non-patent document 3 points out that at the interface between PdCoO2 and a thermally stable oxide, such as the interface between PdCoO2 and β-Ga2O3, a polar layered structure electric dipole is naturally formed, so that even in a high temperature environment such as 350°C, it can be 10 8 A large on / off ratio of the order of 1000 Å realizes current rectification. Furthermore, Non-Patent Document 3 discloses as follows: In the fields of automobiles, factories, and aerospace technology, there is a great demand for high-temperature operation of semiconductor devices for switching and sensing purposes. Prior art literature Patent Literature
[0006] Patent Document 1: International Publication No. 2020 / 090491 Non-patent literature
[0007] Non-patent literature 1: Highly conductive PdCoO2 ultrathin films for transparent electrodes, Harada et al, APL Mater 6, 046107 (2018) Non-patent literature 2: Large thermopower anisotropy in PdCoO2 thin films, Yordanov et al, Phys. Rev. Mater. 3, 085403 (2019) Non-patent literature 3: Electric dipole effect in PdCoO2 / β-Ga2O3 Schottky diodes for high-temperature operation, Harada et al, Science Advances 5, eaax5733 (2019) Summary of the invention Problems to be solved by the present invention
[0008] For example, gallium oxide has a large band gap, a large dielectric breakdown electric field, high thermal stability and excellent chemical resistance, making it an excellent semiconductor for power devices, and the demand for power device applications is expected to increase. However, Schottky electrodes using platinum that have been used in the past have a small Schottky barrier, and the applications of excellent power device semiconductors such as gallium oxide, such as applications requiring high output, are insufficient in terms of heat resistance and reliability (voltage resistance).
[0009] Among them, palladium cobalt oxide (PdCoO2), palladium chromium oxide (PdCrO2), palladium rhodium oxide (PdRhO2) or platinum cobalt oxide (PtCoO2) and other ferromagnetic oxides, although they are oxides, still show high conductivity comparable to single metals such as gold, silver, copper, and are expected to be used as excellent Schottky electrodes for power devices such as gallium oxide. For example, with regard to conductivity, in terms of the resistivity of bulk single crystals (ab plane, 300K), the resistivity (μΩcm) of palladium cobalt oxide, palladium chromium oxide, palladium rhodium oxide and platinum cobalt oxide as ferromagnetic oxides is 2.6, 8.2, 9.2 and 2.1 respectively. Semiconductor devices usually require electrode materials to be deposited as thin films, but for ferromagnetic oxides such as these palladium cobalt oxides, especially when thin films are formed, there is room for improvement in the preparation method that can give full play to the performance. Therefore, it is desirable to provide a ferromagnetic oxide film, such as palladium cobalt oxide, which can be used as a Schottky electrode for power devices, for example.
[0010] The present disclosure is completed in view of the above situation, and its purpose is to provide a palladium cobalt oxide film, a delafossite-type oxide film, a Schottky electrode having a delafossite-type oxide film, a method for preparing a palladium cobalt oxide film, and a method for preparing a delafossite-type oxide film. Means used to solve problems
[0011] The palladium cobalt oxide film disclosed in the present invention for achieving the above-mentioned purpose is as follows: The crystal grain size in the film is 100 nm or more and 1000 nm or less, The thickness exceeds the critical film thickness, and the unevenness in the thickness direction is 4 nm or less.
[0012] The delafossite-type oxide thin film disclosed in the present invention for achieving the above-mentioned purpose is a delafossite-type oxide thin film of palladium chromium oxide (PdCrO2), palladium rhodium oxide (PdRhO2) or platinum cobalt oxide (PtCoO2) with a delafossite-type crystal structure. The crystal width in the film is 100 nm or more and 1000 nm or less, The thickness exceeds the critical film thickness, and the unevenness in the thickness direction is 4 nm or less.
[0013] The Schottky electrode disclosed in the present invention for achieving the above-mentioned purpose has a delafossite-type oxide film such as palladium cobalt oxide (PdCoO2), palladium chromium oxide (PdCrO2), palladium rhodium oxide (PdRhO2) or platinum cobalt oxide (PtCoO2), The crystal grain size in the film is 100 nm or more and 1000 nm or less, the thickness exceeds the critical film thickness, and the unevenness difference in the thickness direction is 4 nm or less.
[0014] The method for preparing the palladium cobalt oxide film disclosed in the present invention for achieving the above-mentioned purpose comprises: A target material preparation step, preparing a palladium cobalt oxide (PdCoO2) target material by sintering a mixed powder of palladium chloride (PdCl2), palladium (Pd) and lithium cobalt oxide (LiCoO2); a film forming step of forming a thin film by sputtering using the target material; The annealing step is to perform heat treatment on the film.
[0015] The method for preparing the delafossite-type oxide film disclosed in the present invention for achieving the above-mentioned purpose comprises: In a film forming step, a target material formed of a delafossite-type oxide of palladium cobalt oxide (PdCoO2), palladium chromium oxide (PdCrO2), palladium rhodium oxide (PdRhO2) or platinum cobalt oxide (PtCoO2) is used to form a thin film by sputtering; The annealing step is to perform heat treatment on the film. Effects of the Invention
[0016] A palladium-cobalt oxide film, a delafossite-type oxide film, a Schottky electrode having a delafossite-type oxide film, a preparation method of the palladium-cobalt oxide film, and a preparation method of the delafossite-type oxide film can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is the AFM morphology image of the PdCoO2 film of Example 1. Figure 2 To show the Figure 1 A diagram showing the evaluation results of the unevenness of the PdCoO2 thin film surface indicated by the straight line M in the middle. Figure 3 This is the X-ray diffraction pattern of the PdCoO2 thin film just formed by sputtering in Example 1. Figure 4 This is the STEM image of the PdCoO2 film of Example 1. Figure 5 This is the X-ray diffraction pattern of the PdCoO2 film of Example 1. Figure 6 Graph showing the temperature dependence of the resistivity of the PdCoO2 thin film of Example 1. DETAILED DESCRIPTION
[0018] With reference to the drawings, a palladium-cobalt oxide thin film, a delafossite-type oxide thin film, a Schottky electrode having the delafossite-type oxide thin film, a method for preparing the palladium-cobalt oxide thin film, and a delafossite-type oxide thin film in embodiments of the present disclosure are described.
[0019] The delafossite oxide film of the present embodiment is a delafossite oxide film of palladium cobalt oxide (PdCoO2), palladium chromium oxide (PdCrO2), palladium rhodium oxide (PdRhO2) or platinum cobalt oxide (PtCoO2) having a delafossite crystal structure. Below, as an example of the delafossite oxide film of the present embodiment, a palladium cobalt oxide film (PdCoO2 film, hereinafter sometimes simply referred to as an oxide film), that is, a film composed of palladium cobalt oxide having a delafossite crystal structure is described as an example. The following description is the same as long as the palladium cobalt oxide having a delafossite crystal structure is replaced by palladium chromium oxide, palladium rhodium oxide or platinum cobalt oxide having a delafossite crystal structure. That is, in palladium cobalt oxide, since A in the general formula ABO2 is Pd and B is Co, for palladium chromium oxide film, palladium rhodium oxide film or platinum cobalt oxide film and their preparation methods, Pd and Co in the description of the palladium cobalt oxide film and its preparation method (including descriptions related to the precursor and raw materials of palladium cobalt oxide) can be replaced by respectively formulating elements corresponding to A and B in palladium chromium oxide, palladium rhodium oxide or platinum cobalt oxide.
[0020] Figure 1 An example of an AFM topography image of the oxide thin film according to the present embodiment is shown. Figure 2 Shown based on Figure 1 The AFM topography image is used to measure the roughness of the oxide film. Figure 2 The evaluation results of the concave and convex shown in the figure show that the Figure 1 The height of the concave and convex measured by the straight line M. Figure 1 and Figure 2 As shown, in the oxide thin film of this embodiment, the width of the PdCoO2 crystal (grain width) in the film is greater than 100nm and less than 1000nm. Considering the preparation of the oxide thin film, the width of the PdCoO2 crystal in the film is preferably greater than 200nm and less than 500nm. Moreover, the thickness of this oxide thin film exceeds the critical film thickness (0.59nm, the film thickness is the thickness of a layer of Pd (A) layer and a layer of CoO2 (BO2) stacked layer by layer), and the unevenness in the thickness direction is less than 4nm (refer to Figure 2 ). In addition, Figure 1 In the figure, the area surrounded by the dotted line (the white part in the figure) is the palladium cobalt oxide crystal. Hereinafter, palladium cobalt oxide may sometimes be simply referred to as PdCoO2. In addition, the critical film thicknesses of palladium chromium oxide, palladium rhodium oxide and platinum cobalt oxide are 0.60nm, 0.60nm and 0.59nm respectively.
[0021] like Figure 1 and Figure 2As shown, in the oxide thin film of this embodiment, the crystal width of palladium cobalt oxide is large (domain size is large), so it shows higher conductivity than the existing palladium cobalt oxide thin film. Therefore, it is suitable for use as a Schottky electrode of a power device.
[0022] As an example, the oxide film of this embodiment can be prepared by the following preparation method: a target material preparation step, preparing a PdCoO2 target by firing a mixed powder of PdCl2, Pd and LiCoO2; a film forming step, using the target material to form a thin film by sputtering; a retreat step, heat treating the formed thin film.
[0023] The target material preparation step is a step for preparing a PdCoO2 target material used in the film forming step. When performing the target material preparation step, a mixing step is first performed to pre-mix PdCl2 powder, Pd powder, and LiCoO2 powder to form a mixed powder. In the target material preparation step, the mixed powder is fired and, if necessary, sintered and formed to prepare a PdCoO2 target material.
[0024] When the mixed powder is fired, cation exchange occurs by the reaction of the following formula (α), thereby generating PdCoO 2 (so-called cation exchange reaction method).
[0025] PdCl2+Pd+2LiCoO2→2PdCoO2+2LiCl(α)
[0026] The particle sizes of the PdCl 2 powder, Pd powder and LiCoO 2 powder used for preparing the mixed powder can be measured on an image by, for example, SEM observation, and a particle size of about several μm to 100 μm can be used.
[0027] The firing in the target material preparation step is carried out at a firing temperature of 500°C to 900°C. The firing in the target material preparation step is preferably carried out at a temperature of 550°C to 800°C. The yield of PdCoO2 can be increased by firing at such a firing temperature, and powdered PdCoO2 can be obtained at the same time. In addition, in the target material preparation step, it is preferably fired in a manner that the particle size of the PdCoO2 powder after firing is 0.1μm to 50μm. The particle size of the PdCoO2 powder after firing is measured on the image observed by SEM, and is 0.1μm to 30μm. By setting the particle size of the PdCoO2 powder after firing as described above, the density of the target material after the following forming is improved, and the operability of the target material is good.
[0028] The firing in the target preparation step may be performed under reduced pressure, or may be performed under atmospheric pressure or in an atmosphere with a high oxygen partial pressure. When firing is performed under reduced pressure, for example, it may be performed under a reduced pressure of 750 mTorr in an AR replacement atmosphere. When firing is performed in an atmosphere with a high oxygen partial pressure, decomposition of the fired powder into Pd and CoO can be suppressed. x (where x is a positive value).
[0029] The above target preparation steps can be used to prepare a PdCoO2 target with higher purity.
[0030] In the target material preparation step, after the above-mentioned firing, a forming step of further sintering and forming the fired powder into a disc shape may be performed. In the forming step, the fired powder may be sintered by applying a pressure of 30 MPa to 70 MPa at a temperature of 550° C. to 800° C. to the fired powder. In the forming step, the sintering may be performed by applying a pressure of 45 MPa to 55 MPa at a temperature of 650° C. to 750° C. to the fired powder. Thus, a disc-shaped target material with good operability can be prepared.
[0031] In addition, in the target material preparation step, PdCoO2 can be used as a sputtering target to shape the PdCoO2 obtained by firing. For example, in the target material preparation method, the pulverization process and the additional shaping process after the synthesis of PdCoO2 are sometimes not required.
[0032] In the target preparation step, after firing, the fired powder can be washed with ethanol and acid. Lithium chloride and other impurities can be removed by washing the fired powder with ethanol and acid. Lithium chloride is removed by ethanol washing. Unreacted Pd powder (metal palladium) is removed by acid washing. Acid washing can use nitric acid (e.g., concentration 60 weight percent).
[0033] In the target material preparation step, the fired powder can be crushed as needed to adjust the particle size of the fired powder. For example, if the particle size of the fired powder is adjusted to the order of several μm, the density of the target material after forming described below can be improved.
[0034] The film forming step is a step of forming a PdCoO 2 thin film by a sputtering method using the target prepared in the target preparing step.
[0035] An example of a sputtering method that is preferable in the film forming step is an RF sputtering method in which a high-frequency AC voltage is applied to a target and a chamber that accommodates the target.
[0036] In the film forming step, the sputtering conditions when forming the PdCoO2 thin film by RF sputtering are as follows: the oxygen partial pressure during sputtering is 50 mTorr or more and 250 mTorr or less; preferably 80 mTorr or more and 120 mTorr or less. The substrate temperature during sputtering is 500°C-800°C; preferably 550°C-700°C. In addition, as a substrate for forming the PdCoO2 thin film, for example, an Al2O3 (0001) substrate, that is, a sapphire substrate (wherein the (0001) plane is used) can be used.
[0037] By performing the film forming steps as described above, even when forming a thin film of, for example, 20 nm or less, a thin film of PdCoO2 having a large crystal grain size can be obtained. Furthermore, the thin film has high flatness, the crystals are C-axis oriented, and the crystallinity is high.
[0038] After that, the thin film formed in the film forming step is subjected to an annealing step and heat treatment. Through the heat treatment, a PdCoO2 thin film that does not contain metal palladium and has a low resistivity can be obtained. In addition, the PdCoO2 thin film has a high degree of crystallinity.
[0039] Furthermore, in the present embodiment, the PdCoO2 film does not contain metallic palladium and cobalt oxide means that when comparing the intensity of the peak of diffraction X-rays at the diffraction angle (40.1°) corresponding to the (111) plane of metallic palladium and the diffraction angle (about 38.6°) corresponding to Co3O4 (222) observed by, for example, X-ray diffraction (XRD) with the intensity of the peak of diffraction X-rays at the diffraction angle (30.2°) corresponding to the (0006) plane of PdCoO2, the intensity of the peak of diffraction angles (about 38.6°) corresponding to the (111) plane of metallic palladium and Co3O4 (222) is less than 1 / 100 of the intensity of the peak of diffraction X-rays corresponding to (0006) of PdCoO2.
[0040] The heat treatment in the annealing step may be preferably performed at a temperature of 600° C. to 800° C., preferably 650° C. to 700° C. Therefore, a PdCoO2 thin film containing no metal palladium and having a low resistivity can be appropriately obtained.
[0041] The oxide thin film of this embodiment preferably has a thickness of 1 nm to 20 nm. Such an oxide thin film is suitable as a Schottky electrode.
[0042] In the above description, the delafossite oxide thin film, the Schottky electrode having the delafossite oxide thin film, and the method for preparing the delafossite oxide thin film are described using the palladium cobalt oxide thin film as an example, but as mentioned at the beginning, the description using these palladium cobalt oxide thin films as examples is the same as that of the palladium chromium oxide thin film, the palladium rhodium oxide thin film, or the platinum cobalt oxide thin film. Furthermore, the method for preparing these thin films and the Schottky electrode using these thin films are also the same as that of the palladium cobalt oxide thin film and the Schottky electrode using the palladium cobalt oxide thin film. Example
[0043] (Example 1) The palladium cobalt oxide thin film of Example 1 was prepared as follows.
[0044] 8.99 g, 5.39 g and 9.92 g of PdCl2 powder (manufactured by Tanaka Kikinzoku Kogyo Co., Ltd., Pd chloride crystals, Pd powder (manufactured by Tanaka Kikinzoku Kogyo Co., Ltd., Pd powder, Pd purity exceeding 99.9%) and LiCoO2 powder (manufactured by Sigma-Aldrich, lithium cobalt (III) oxide) were weighed respectively, and these were mixed in a mortar for 10 minutes to obtain a mixed powder. In addition, the particle size of the LiCoO2 powder was about several μm to tens of μm in the measurement on the image observed by SEM.
[0045] Next, the mixed powder was vacuum sealed in a quartz tube (about 10 -5 Torr), the quartz tube is further contained in a holding tube made of mullite. Furthermore, the holding tube is contained in a firing furnace equipped with a furnace core tube made of mullite. The temperature of the furnace core tube of the firing furnace is controlled to be maintained at 800°C. Furthermore, the firing is performed for 48 hours. Furthermore, the powder containing PdCoO2 is recovered from the quartz tube.
[0046] Lithium chloride was removed from the powder containing PdCoO2 with ethanol (ethanol washing), and unreacted Pd was further removed with nitric acid (concentration 60 weight percent) (acid washing) to obtain PdCoO2 powder. The recovery amount of PdCoO2 powder was 17.58g. In addition, during the ethanol washing, the powder containing PdCoO2 was stirred in ethanol for 1 hour. During the acid washing, it was stirred in nitric acid for 4 hours. The particle size of the PdCoO2 powder was about 1μm-50μm in the measurement on the image observed by SEM.
[0047] Next, the PdCoO2 powder is filled into the mold and sintered by hot pressing under pressure to obtain a disc-shaped target. The pressure during sintering (the pressure applied to the powder) is 50 MPa. The temperature in the sintering furnace during sintering is maintained at 700°C for 60 minutes. In addition, the sintering furnace is a vacuum atmosphere.
[0048] Next, using the disc-shaped target obtained above, a PdCoO2 thin film was formed by RF sputtering. Considering the operability when used in a sputtering device, the target was placed in the chamber of the sputtering device in a state attached to a copper plate backing plate (diameter 50.8 mm, thickness 2 mm). The substrate on which the thin film is formed is an Al2O3 (0001) substrate (hereinafter referred to as the substrate). The atmosphere in the chamber during sputtering was 150mTorr (oxygen partial pressure in the chamber was 100mTorr), the ratio of oxygen to argon was 2:1, and the substrate temperature was 700°C. The high-frequency output was 100W and the frequency was 13.56MHz. The target film thickness of the PdCoO2 thin film was 15nm. The PdCoO2 thin film formed by sputtering was evaluated by X-ray diffraction. Figure 3 The X-ray diffraction pattern of a thin film just formed by sputtering is shown. Figure 3 .
[0049] The substrate with the PdCoO2 thin film formed as described above was placed in a heating furnace controlled at 800°C, heat treated for 12 hours under atmospheric pressure, and then taken out of the furnace to prepare the palladium cobalt oxide thin film of Example 1. In the following description, when simply referred to as a thin film, it means the thin film after heat treatment.
[0050] The film thickness of the thin film was measured, and further, the surface flatness was observed by AFM, and the X-ray diffraction method and resistivity were evaluated.
[0051] The film thickness of the thin film was 15 nm. The film thickness was determined based on the detection of interference fringes near the diffraction point of PdCoO2 (0006) by X-ray diffraction.
[0052] The results of observing the surface shape of the film by AFM (AFM morphology image) are as shown above. Figure 1 and Figure 2 As shown. In this film, the width of the PdCoO2 crystal in the film is about 400nm. In addition, in this film, the height of the crystal and the difference in the concave and convex (peak difference) in the thickness direction (height direction) of the film surface are about 3nm. In addition, the PdCoO2 crystal in the film has a triangular shape.
[0053] also, Figure 1 The AFM topography images shown were taken using an AFM5000II atomic force microscope manufactured by Hitachi High-Technologies Corporation in dynamic force mode (DFM).
[0054] Figure 4A HAADF-STEM (High-Angle Annular Dark Field Scanning TEM) image (hereinafter referred to as a STEM image) of a cross section of the film is shown. The STEM image was taken using a Titan cubed manufactured by FEI at an accelerating voltage of 300 kV. Figure 4 The carbon film in the cross section shown originates from covering the cross section of the thin film during TEM observation rather than from the thin film. Figure 4 In the cross-sectional portion of the PdCoO2 film in the STEM image shown, Pd atoms and Co atoms are arranged in a delafossite structure. Concave portions (e.g., Figure 4 The concave portion and the like in the thickness direction of the thin film have a concave-convex difference (for example, the depth t of the concave portion on the X portion) far below 4 nm.
[0055] Next, the thin film was evaluated by X-ray diffraction. Figure 5 An X-ray diffraction pattern of the thin film of Example 1 is shown.
[0056] As mentioned above, Figure 3 1 shows an X-ray diffraction pattern of a thin film just formed by sputtering in Example 1. Figure 3 As shown in the X-ray diffraction pattern of the thin film just formed by sputtering, Figure 3 The peaks represented by symbols a to g in the graph are in the following order: symbol a: PdCoO2 (0003); symbol b: sapphire substrate; symbol c: PdCoO2 (0006); symbol d: Pd (111); symbol e: sapphire substrate; symbol f: PdCoO2 (0009). In addition, no peaks related to other impurities were observed in the thin film just formed by the sputtering method.
[0057] Figure 5 The X-ray diffraction pattern of the film of Example 1 shown is Figure 3 The following peaks are also observed: symbol a: PdCoO2 (0003); symbol b: sapphire substrate; symbol c: PdCoO2 (0006); symbol e: sapphire substrate; symbol f: PdCoO2 (0009). Figure 5In the embodiment 1, at the diffraction angle corresponding to Pd (111) (about 40.1°) and the diffraction angle corresponding to Co3O4 (222) (about 38.6°), the intensity of the diffracted X-ray is at least 1 / 100 of the intensity of the peak of the diffracted X-ray corresponding to (0006) of PdCoO2, and it cannot be separated from the baseline, and the peak of the diffracted X-ray cannot be identified. That is, it is believed that the film does not contain metal palladium and cobalt tetraoxide to the extent that can be detected by X-ray diffraction. In addition, in the film of Example 1, no peaks related to other impurities can be confirmed.
[0058] Figure 6 A graph showing the temperature dependence of the resistivity of the film. Figure 6 The graph shown is a value obtained by measuring the resistivity corresponding to each temperature while increasing the film temperature from 2K absolute temperature to 400K absolute temperature. In addition, the resistivity was measured as follows: that is, wiring was performed using Au (gold) wires by In (indium) crimping, and the temperature dependence of the sheet resistance was measured using a DC four-terminal method. The film thickness (about 15nm) obtained by the above method was converted using an X-ray diffraction method to obtain the volume resistivity (μΩ·cm).
[0059] like Figure 6 As shown, in the thin film of Example 1, the resistivity at an absolute temperature of 2K-150K is 3 μΩcm or more and 6 μΩcm or less.
[0060] Furthermore, in the thin film of Example 1, when the absolute temperature is T (K) and the resistivity is R (μΩcm), the resistivity at an absolute temperature of 2K-400K satisfies the following formula (1).
[0061] R<0.025×T+5(1)
[0062] Thus, the thin film of Example 1 has low resistivity and high conductivity even in a thin film state. In addition, since the resistivity of platinum is 9.81 μΩcm at an absolute temperature of 273K and 13.6 μΩcm at an absolute temperature of 373K, it can be seen that the thin film of Example 1 shows high conductivity comparable to that of a single metal even if it is formed into a thin film of less than 20nm, such as 15nm. Therefore, it is considered to be very suitable for use as a Schottky electrode in combination with, for example, gallium oxide. For example, from Figure 1 and Figure 2 From the observation results of the surface shape shown, it can be seen that the high conductivity in the film of Example 1 is due to the fact that in the film of Example 1, the PdCoO2 crystal grain size in the film is larger than the PdCoO2 crystal grain size in the PdCoO2 film formed by the prior art, so this is considered to be achieved because the boundaries between particles become smaller and the resistance between the boundaries becomes smaller.
[0063] Furthermore, the thin film of Example 1 does not contain metal palladium and other impurities, and it is believed that it can be prepared with high reproducibility. Moreover, since such impurities are not contained, it is believed that when used in combination with gallium oxide or the like for Schottky electrode applications, the high thermal stability and excellent chemical resistance of gallium oxide will not be impaired, and for example, heat resistance and reliability can be achieved even in applications requiring high output.
[0064] The pulse laser deposition method disclosed in non-patent documents 1-3 is not suitable for forming a large-area thin film. As pointed out in non-patent document 2, it is difficult to form a large-area palladium cobalt oxide thin film industrially using the pulse laser deposition method. However, as described above, in the preparation method of the palladium cobalt oxide thin film of the present embodiment, since the sputtering method is used to form the film of the PdCoO2 thin film, it is easy to form a large-area palladium cobalt oxide thin film, which is suitable for industrial production.
[0065] Furthermore, compared to the formation of a palladium cobalt oxide film by the pulsed laser deposition method disclosed in non-patent literature 1-3, in the preparation method of the palladium cobalt oxide film of the present embodiment, unlike the pulsed laser deposition method disclosed in non-patent literature 1-3, there is no need to use two targets of different compositions, and only one target can be used to form a palladium cobalt oxide film. Therefore, the preparation of the film is simplified in the preparation method according to the embodiment. Furthermore, if two targets of different compositions are used, it is difficult to stably form a palladium cobalt oxide film having the same composition or crystal structure (in other words, the reproducibility of the preparation becomes low). However, since the palladium cobalt oxide film can be prepared using only one target in the preparation method of the present embodiment, it is easy to stably form a palladium cobalt oxide film having the same composition or crystal structure, and since it is easy to improve the reproducibility of the preparation, this is preferred.
[0066] If the common properties of bulk single crystals of palladium cobalt oxide, palladium chromium oxide, palladium rhodium oxide and platinum cobalt oxide as delafossite-type oxides and the common properties with palladium, platinum, chromium, cobalt and rhodium are considered, then the matters related to the preparation method of the palladium cobalt oxide thin film, the Schottky electrode having the palladium cobalt oxide thin film and the palladium cobalt oxide thin film confirmed by the embodiments described above are naturally considered to be common to delafossite-type oxides such as palladium chromium oxide, palladium rhodium oxide and platinum cobalt oxide other than palladium cobalt oxide.
[0067] As described above, a palladium-cobalt oxide thin film, a delafossite-type oxide thin film, a Schottky electrode having a delafossite-type oxide thin film, a method for preparing a palladium-cobalt oxide thin film, and a method for preparing a delafossite-type oxide thin film can be provided.
[0068] In addition, the embodiments disclosed herein are exemplary, and the embodiments of the present disclosure are not limited thereto, and may be appropriately modified within the scope not departing from the purpose of the present disclosure. Industrial Applicability
[0069] The present disclosure is applicable to a palladium-cobalt oxide film, a delafossite-type oxide film, a Schottky electrode having a delafossite-type oxide film, a method for preparing a palladium-cobalt oxide film, and a method for preparing a delafossite-type oxide film.
Claims
1. A palladium cobalt oxide thin film, characterized in that: The crystal width in the film is 100 nm or more and 1000 nm or less, The thickness exceeds the critical film thickness, and the unevenness in the thickness direction is 4 nm or less.
2. The palladium cobalt oxide thin film according to claim 1, characterized in that The resistivity at absolute temperature 2K-150K is below 6μΩcm. When the absolute temperature is set to T (K) and the resistivity is set to R (μΩcm), the resistivity at the absolute temperature of 150K-400K satisfies the following formula (1): R<0.025×T+5(1).
3. The palladium cobalt oxide thin film according to claim 1 or 2, characterized in that: Contains no metallic palladium crystals or cobalt tetroxide.
4. The palladium cobalt oxide thin film according to any one of claims 1 to 3, characterized in that The film thickness is 20 nm or less.
5. A delafossite-type oxide film of palladium chromium oxide (PdCrO2), palladium rhodium oxide (PdRhO2) or platinum cobalt oxide (PtCoO2) having a delafossite-type crystal structure, characterized in that: The crystal width in the film is 100 nm or more and 1000 nm or less, The thickness exceeds the critical film thickness, and the unevenness in the thickness direction is 4 nm or less.
6. A Schottky electrode having a delafossite-type oxide film of palladium cobalt oxide (PdCoO2), palladium chromium oxide (PdCrO2), palladium rhodium oxide (PdRhO2) or platinum cobalt oxide (PtCoO2), characterized in that: The crystal grain size in the film is 100 nm or more and 1000 nm or less, the thickness exceeds the critical film thickness, and the unevenness difference in the thickness direction is 4 nm or less.
7. A method for preparing a palladium cobalt oxide thin film, characterized in that: include: A target material preparation step, preparing a palladium cobalt oxide (PdCoO2) target material by sintering a mixed powder of palladium chloride (PdCl2), palladium (Pd) and lithium cobalt oxide (LiCoO2); a film forming step of forming a thin film by sputtering using the target material; The annealing step is to perform heat treatment on the film.
8. The method for preparing a palladium cobalt oxide thin film according to claim 7, characterized in that: In the annealing step, the thin film is heat-treated at a temperature of 600°C to 800°C.
9. A method for preparing a delafossite-type oxide film, characterized in that: include: In a film forming step, a target material formed of a delafossite-type oxide of palladium cobalt oxide (PdCoO2), palladium chromium oxide (PdCrO2), palladium rhodium oxide (PdRhO2) or platinum cobalt oxide (PtCoO2) is used to form a thin film by sputtering; The annealing step is to perform heat treatment on the film.
Citation Information
Patent Citations
Power device-sealing resin composition and power device
WO2020090491A1
Cited By
Metal delafossite PdRhO2 film and preparation method thereof
CN120089461A